2010
DOI: 10.1007/s00421-010-1463-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of ventilation from measurements of rib cage and abdominal distances: a portable device

Abstract: To validate a new device designed to measure ventilation (V(E)), tidal volume (V(T)), inspiratory time (T(I)), and expiratory time (T(E)) during daily life activities. The anteroposterior displacement of the rib cage and abdomen and the axial displacements of the chest wall and the spine were measured using two pairs of magnetometers. was estimated from these four signals, and was simultaneously measured using a spirometer. A total of 707, 732, and 1,138 breaths were analyzed in sitting, standing, and exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…A new device (Nomics-WSL2, Liege Science Park, Belgium) has been developed so as to estimate _ V E (Gastinger et al 2010a). This device is made up of two pairs of electromagnetic coils securely connected to a case.…”
Section: Non-invasive Methods To Estimate Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…A new device (Nomics-WSL2, Liege Science Park, Belgium) has been developed so as to estimate _ V E (Gastinger et al 2010a). This device is made up of two pairs of electromagnetic coils securely connected to a case.…”
Section: Non-invasive Methods To Estimate Ventilationmentioning
confidence: 99%
“…The development of a group equation could be an interesting solution that would increase the feasibility of our method under daily life conditions. Given the high correlation between _ VO 2 and indirect calorimetry-assessed EE described in the literature (Harrell et al 2005;Macfarlane 2001;Montoye et al 1996), the validity of the _ V E method for estimating _ VO 2 (Gastinger et al 2010b) and the validation of the measurement of _ V E from two pairs of electromagnetic coils (Gastinger et al 2010a) (Fig. 1), the aims of our study are: (1) to ensure the validity of electromagnetic coils so as to estimate EE under resting and moderate exercise conditions and (2) to prove the feasibility of our method of estimating EE from the application of a group equation in comparison with the individual equations.…”
Section: Introductionmentioning
confidence: 98%
“…Similar to our study, the estimation technique used by Witt et al was low on precision (Witt et al, 2006). In comparison, Gastinger et al reported similar bias (−1.03 L˙min −1 ) but better precision (95% limits of agreement= −8.23 to 6.17 L˙min −1 ) in predicting ventilation volume (Gastinger et al, 2010). The activities performed in the studies by Witt et al and Gastinger et al were limited to rhythmic ambulatory activities and did not induce a lot of variability in respiration.…”
Section: Discussionmentioning
confidence: 89%
“…28,29 Another approach within occupations that use breathing apparatus to provide an uncontaminated, self-contained air supply is to use Boyle's Law to calculate the volume of gas inspired over the work duration, and an average minute ventilation. Unfortunately, such measures are difficult in the field, although portable monitors are available to quantify chest-wall displacement.…”
Section: Discussionmentioning
confidence: 99%